FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIARE PADA BAYI USIA 6-12 BULAN DI WILAYAH KERJA PUSKESMAS KETANGGUNGAN KABUPATEN BREBES TAHUN 2024 - Hartini, Sri (Jurnal Kesehatan Borneo Cendekia, 2024)
ABSTRACT Background: Diarrhea is one of the main causes of morbidity and mortality in children throughout the world, especially in children under five years of age which often occurs in developing countries. Diarrhea cases in toddlers in Indonesia in 2019 were 1,605,493 cases. In 2020 there were 1,140,503 cases, in 2021 it decreased to 818,687 cases and in 2022 the number of cases of toddler diarrhea increased by 974,268 cases. The prevalence of diarrhea in Central Java is in the 3rd highest category with 86,093 in 2022, Brebes Regency is in the 13th highest with 852 cases of under-five diarrhea in 2024, the highest prevalence is in the work area of ​​the Ketanggungan Primary Health Care Center with a percentage of 13.25% of diarrhea cases. with direct and indirect causes. Diarrhea management is one of the government programs of the Ministry of Health of the Republic of Indonesia, known as Lima Langkah Tuntaskan Diare (LINTAS diare) as one of the strategies for controlling diarrheal disease in Indonesia. Purpose: To determine the factors associated with the incidence of diarrhea in infants aged 6-12 months Method: Analytical survey research using a cross-sectional approach. The population was 387 babies, with a sample of 76 mothers of babies aged 6-12 months. Results: 40.8% of respondents had little knowledge about diarrhea, 44.7% of respondents did not give exclusive breast milk to their babies, 51.3% of respondents did not wash their hands without using soap. Conclusion: the majority of respondents have good knowledge, the majority have a supportive attitude, the majority are given exclusive breastfeeding and the majority wash their hands without soap. There is a relationship between knowledge, attitude, exclusive breastfeeding and hand washing with the incidence of diarrhea. Keywords: Diarrhea, Toddlers, Diarrhea in toddlers